Biological properties of neural crest-derived multipotent stem cells from the bulge region of whisker follicle expanded in new culture conditions - Vasyliev, R.G.; Rodnichenko, A.E.; Zubov, D.A.; Rymar, S.Y.; Gubar, O.S.; Labunets, I.F.; Novikova, S.N. (Вiopolymers and Cell, 2014)
Aim. The work is aimed at obtaining the culture of neural crest-derived multipotent stem cells (NC-MSCs) in new culture conditions and to investigate their biological properties. Methods. NC-MSCs were grown from the explants of the bulge region of whisker follicle of adult mice. The cell cultures were examined by the following methods: sphere-forming assay, directed multilineage differentiation, CFU assay, immunocytochemistry, flow cytometry, RT-PCR. Results. The obtained NC-MSCs expressed the typical neural crest markers (nestin, Sox10 and Sox2) and were differentiated into adipocytes, osteoblasts and Schwann cells. Under our original growing conditions, the culture of NC-MSCs at the third passage had the following parameters: 66.8 % nestin+, 3.1 % ALDH brigth and 33.3 % clonogenic cells. The NC-MSCs growth rate depended on plating density. EGF and bFGF demonstrated a dose-dependent mitogenic action on NC-MSCs. Conclusions. The proposed approach permits the NC-MSC expansion with the maintenance of their main functional properties. Further optimization of the culture conditions will be based on the use of growth factors and low plating density.